Penggunaan Progesteron untuk Sinkronisasi Birahi pada Rusa Chital (Axis axis) Dievaluasi Menggunakan Progesterone Radio Immunoassay (THE USE OF PROGRESTERONE IN INDUCING ESTROUS SYNCHRONIZATION IN CHITAL DEER (AXIS AXIS) EXAMINED BY PROGESTERONE RADIO IM - Dradjat, Adji Santoso (Jurnal Veteriner; Vol 2 No 1 (2001), 2016)
Penggunaan Progesteron untuk Sinkronisasi Birahi pada Rusa Chital ( Axis axis ) Dievaluasi Menggunakan Progesterone Radio Immunoassay   (THE USE OF PROGRESTERONE IN INDUCING ESTROUS SYNCHRONIZATION IN CHITAL DEER (AXIS AXIS) EXAMINED BY PROGESTERONE RADIO IMMUNOASSAY)
Keywords: Chital deer, progesterone, estrous synchronization